REKAYASA FIP (FUNDAMENTAL OF IMAGE PROCESSING) BERBASIS MATLAB MOBILE (Information Technology and Telematics, 2016)
Abstract Engineering FIP (Fundamentals Of Image Processing) Based MATLAB Mobile is a process connection network Matlab desktop with Matlab mobile to utilize the functionality basics of digital image processing as objects connectivity test as a binary function, grayscale function, negative function, rotation function, flipping function  and clipping function  with based on Matlab mobile.The purpose of this study was to develop a mobile connectivity matlab mobile in FIP (Fundamentals of Image Processing) by utilizing the basics of image processing as the connectivity test. Systems Development Method used the method of SLC (System Life Cycle) is an evolutionary process that is followed by the implementation of information systems basics or subsystems . Engineering FIP (Fundamentals Of Image Processing) Based Matlab Mobile was built using  software Matlab desktop and Matlab Mobile.This research has resulted in connectivity between Matlab on the desktop and Mobile that can perform the function of the basics of image processing on the desktop and in mobile While the object test connectivity using the functions of the basics of image processing such as binary  function, grayscale function , negative function, rotation function, flipping function  and clipping function.  Keywords: Image Processing, FIP, Matlab Desktop, Matlab Mobile